Determinants of shooting velocity in elite team handball players - Karcher, C.; Pierrat, T.; Schoffit, C.; Hureau, T. J. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
The purpose of this study was to determine the major determinants of shooting velocity for the three main shooting conditions observed in handball (standing shots, running shots and jumping shots). To this end, shooting performances were correlated (multiple regressions) to upper body (strength, anthropometrics, goniometry) and lower body (sprints and jumps) performances/characteristics. While upper body strength contributed to shooting velocity (both pushing and pulling), lower body performances did not.